Impact of anthropogenic global hypoxia on the physiological response of bivalves - Jingjing Song; Ardavan Farhadi; Kianann Tan; Lim, Leong Seng; Karsoon Tan (Elsevier BV, 2024)
Dissolved oxygen (DO) is an important parameter that affects the biology, physiology, and immunology of aquatic animals. In recent decades, DO levels in the global oceans have sharply decreased, partly due to an increase in atmospheric carbon dioxide, temperature, and anthropogenic nutrient loads. Although there have been many reports on the effects of hypoxia on the survival, growth, behavior, and immunity of bivalves, this information has not been well organized. Therefore, this article provides a comprehensive review of the effects of hypoxia on bivalves. In general, hypoxia negatively impacts the food consumption rate and assimilation efficiency, as well as increasing respiration rates in many bivalves. As a result, it reduces the energy allocation for bivalve growth, shell formation, and reproduction. In severe cases, prolonged exposure to hypoxia can result in mass mortality in bivalves. Moreover, hypoxia also has adverse effects on the immunity and response of bivalves to predators, including decreased burial depths, sensitivity to predators, impairment of byssus production, and negatively impacts on the integrity, strength, and composition of bivalve shells. The tolerance of bivalves to hypoxia largely depends on size and species, with larger bivalves being more susceptible to hypoxia and intertidal species being relatively more tolerant to hypoxia. The information in this article is very useful for elucidating the current research status of hypoxia on bivalves and determining future research directions.